Ehe, Familie und Agamie. Die Begründung von Lebensformen angesichts gesellschaftlicher Pluralität im Neuen Testament und heute Matthias Becker: Tübingen: Mohr Siebeck, 2024; x + 239 pp, € 29,00 €, pb; ISBN 9783161625428 - Grassl, Fabian F. (2025)
Matthias Becker skilfully guides his readers through the copious source material from classical antiquity and the New Testament, delineating a well-founded picture of ancient patterns of thought and rendering valuable service to contemporary debates on sexual ethics. In three sections he presents 1) the plurality of the Roman Empire with its diverse views of marriage, the family and sexuality; 2) the arguments of the authors of the New Testament for the three recognised ideal life forms (marriage, family and celibacy) and 3) hermeneutical impulses for ethical reflection in the present. Becker’s study solidly anchors current attempts to base genuine Christian life models in history and in the process exposes myths which distort the current debate on sexual ethics.
Keywords: Rezension